Volume Transport Time Series and Variability of the North Atlantic Eastern Boundary Current at Goban Spur - Moritz, Martin; Jochumsen, Kerstin; Kieke, Dagmar; Klein, Birgit; Klein, Holger; Köllner, Manuela; Rhein, Monika; Jochumsen, Kerstin; 1 Federal Maritime and Hydrographic Agency (BSH) Hamburg Germany; Kieke, Dagmar; 2 Institute of Environmental Physics University of Bremen Bremen Germany; Klein, Birgit; 1 Federal Maritime and Hydrographic Agency (BSH) Hamburg Germany; Klein, Holger; 1 Federal Maritime and Hydrographic Agency (BSH) Hamburg Germany; Köllner, Manuela; 1 Federal Maritime and Hydrographic Agency (BSH) Hamburg Germany; et al. (Journal of Geophysical Research: Oceans, 2021)
The Eastern Boundary Current is an essential part of the water mass exchange between the subtropical and subpolar North Atlantic. Here, we study the offshore branch of the European Shelf Current (ESC) over the Goban Spur slope area off Ireland. Our analysis is based on current measurements obtained from a multiyear mooring effort, complemented by ship‐board observations along a hydrographic section, satellite‐derived estimates of absolute dynamic topography with geostrophic currents, and float trajectories. These data serve to quantify the offshore branch of the ESC on intraannual to interannual timescales. From the moored observations, we derive a mean poleward along‐slope volume flux of 3.7 ± 0.7 Sv for the period 2017–2019. Using a multilinear regression model and geostrophic surface velocities, we extend the time series to the period 1993–2019 and obtain a long‐term mean transport of 3.2 ± 0.4 Sv. Both time series show strong variability ranging from −7.5 to 15.7 Sv. The variability is linked to a dynamic eddy field, especially a stationary cyclonic circulation pattern near the mooring array, and meandering of current branches originating from the North Atlantic Current. We find no evidence of a consistent deep boundary current extending from the shelf break to the position of the offshore mooring (4,500 m depth), but confirm a persistent along‐slope flow at the shallower slope (1,500 m depth). Geostrophic surface velocities and float trajectories reveal that the offshore branch of the ESC does not follow a clear northward path from the eastern subtropical regions but rather indicate the intermittent character of the flow. Plain Language Summary: In this study, we describe the European Shelf Current (ESC) in the eastern North Atlantic. The study area is the deeper part of the Goban Spur area off Ireland. We use current measurements of instruments deployed in the water column from 2016 to 2019 combined with satellite observations of surface circulation and drifting float paths. We aim to quantify the ...